2013
DOI: 10.1016/j.watres.2013.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Chronic impact of tetracycline on the biodegradation of an organic substrate mixture under anaerobic conditions

Abstract: 24The study evaluates the chronic impact of the antibiotic tetracycline on the biodegradation of 25 organic substrate under anaerobic conditions. The experiments involved an anaerobic 26 M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT2 sequencing batch reactor fed with a synthetic substrate mixture including glucose, starch and 1 volatile fatty acids, and operated in a sequence of different phases with gradually increasing 2 tetracycline doses of 1.65 -8.5 mg/L, for more than five months. Tetracycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(57 citation statements)
references
References 28 publications
1
53
0
3
Order By: Relevance
“…Tetracyclines are reported to show a strong sorption to biosolids such as soil or activated sludge (Hamscher et al, 2002;Prado et al, 2009). In one study using anaerobic conditions, only a minor sorption to the digester sludge was reported (Cetecioglu et al, 2013). As already discussed for sulfadiazine (see Section 3.2.2.…”
Section: Tetracyclinesmentioning
confidence: 88%
See 2 more Smart Citations
“…Tetracyclines are reported to show a strong sorption to biosolids such as soil or activated sludge (Hamscher et al, 2002;Prado et al, 2009). In one study using anaerobic conditions, only a minor sorption to the digester sludge was reported (Cetecioglu et al, 2013). As already discussed for sulfadiazine (see Section 3.2.2.…”
Section: Tetracyclinesmentioning
confidence: 88%
“…manure, activated sludge, biogas plant fermenter content), the initial compound concentration, or the duration of the experiment. In some cases no influence was found, whereas other studies revealed a decrease of the biogas and/or methane yield (Álvarez et al, 2010;Bauer et al, 2014;Cetecioglu et al, 2013;Lallai et al, 2002;Massé et al, 2000;Mitchell et al, 2013;Mohring et al, 2009;Sara et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, the removal and biodegradability of SMX in anaerobic systems has not been widely studied. There are few studies regarding the anaerobic biodegradability characteristics of SMX in the literature (Gartiser et al, 2007;Cetecioglu, et al, 2013;Aydin et al, 2015;Martín et al, 2015). Gartiser et al (2007) assessed the biodegradability of the selected antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, many antibiotics can be easily entered into the environment because of the poor absorption, low metabolism, abuse and overuse. Antibiotics in environment could cause lots of direct toxicities and potential risks (the effects include the development of super bacteria, direct or indirect toxicity to microorganism and possible risks to human beings) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%